Level amputation definition of the lower limbs by means of a technique identification of muscles ischemic damages in a chronic critical ischemia patients - V. V. Kochubey (Бюллетень сибирской медицины, 2010)
Results of application of a technique identification of ischemic damages of muscles are described, confirming its reliability for a choice of level of amputation concerning a chronic critical ischemia.